HCI in business, government and organizations : 6th International Conference, HCIBGO 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings /: 6th International Conference, HCIBGO 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings. ([2019]) - Unknown
No abstract available